Development of Argumentative Learning Model Procedures Inquiry Blended Learning on Acid-Base Materials - Feronica Purba; Harizon Harizon; Muhammad Haris Effendi (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Argumentation skills play a major role in developing critical thinking skills and understanding problems and ideas. Argumentation ability is one of the most complex thinking skills in the learning process. The purpose of this study was to determine the procedure for developing an argumentative inquiry blended learning model on acid-base material. The research method used the "Research and Development" (R D) method. The research procedure for developing a procedural learning model uses the type of procedure type F2-O2-S4-A3. The Argumentative Learning Model Procedure produced in this study is a combination of the Inquiry Argumentative Learning Model and the blended learning model using one type of research procedure for the development of Lee J.L and Jang with Type F2-O2-S4-A3. The conclusion of the study is that this development design model went through several stages, namely the stage of determining data sources, collecting data, analyzing data, generating ideas, describing models, urgency of procedures, concept validation, providing recommendations for testing procedures, practical validation, describing model II.